2012
DOI: 10.4067/s0717-95022012000100010
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Processus Vaginalis!: The Abdomino Scrotal Hydrocoele

Abstract: SUMMARY:A knowledge of the embryology and descent of the testes is essential for all clinicians. Congenital hydrocoele, though an embryologic anomaly can present in adulthood. A abdomino scrotal hydrocole must be considered when a mass in the lower abdomen co exists with a scrotal hydrocoele.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Almost all researchers have found that the incidence of vaginal process permeability is highest in childhood. A persistent vaginal process has been found to be present in 80-95% of all male newborns, in 60% of 1-year-olds and decreasing to 40% in 2-year-olds, thereafter being seen in 15-37% [8] . According to some statistics, the incidence of asymptomatic patent vaginal process in Vietnamese adults is about 7.1% in men, and in women, this rate varies between 12.1% and 3.0%, being observed more frequently on the right side [9] .…”
mentioning
confidence: 98%
“…Almost all researchers have found that the incidence of vaginal process permeability is highest in childhood. A persistent vaginal process has been found to be present in 80-95% of all male newborns, in 60% of 1-year-olds and decreasing to 40% in 2-year-olds, thereafter being seen in 15-37% [8] . According to some statistics, the incidence of asymptomatic patent vaginal process in Vietnamese adults is about 7.1% in men, and in women, this rate varies between 12.1% and 3.0%, being observed more frequently on the right side [9] .…”
mentioning
confidence: 98%